Influence of strain on the dielectric properties of Bi-Zn-Ti-Nb-O solid solution thin films - Kim, Jin Young; Kim, Dong-Wan; Jung, Hyun Suk; Hong, Kug Sun (ELSEVIER SCI LTD, 2006)
Bi-Zn-Ti-Nb-O (BZTN) solid solution thin films with various compositions were prepared by metalorganic decomposition (MOD) process on the platinized Si substrates. BZTN thin films showed a wide solid solubility since the thin films maintained the single phase of cubic pyrochlore structure in a broad range of composition. Crystal structure and dielectric properties of BZTN thin films were compared to those of BZTN bulk ceramics and the difference in dielectric properties such as dielectric constant, dielectric loss and tunability between thin films and bulk ceramics were understood to originate from the strain in the thin films since there was no apparent difference in the other factors such as microstructure and preferred orientation. The existence of strain in the thin films was confirmed by two ways. One is the rate of lattice shrinking. Shrinkage in the lattice parameter of thin films was depressed compared to that of bulk ceramics, which might introduce the internal strain in the thin films. Another is the thermal expansion coefficient (alpha, TEC) of BZTN solid solutions. TEC measured from the bulk ceramics varied with composition and the difference in the TEC between the polycrystalline thin film and underlying substrate would result in the thermal strain of thin films. Thin films with various compositions were under different degree of tensile stress state and the BZTN thin films with optimal composition demonstrated the high tunability of 30% under 1100 kV/cm with dielectric constant of 242 and dielectric loss of 0.004. (c) 2005 Elsevier Ltd. All rights reserved.